Could PGT-A pick up true abnormalities that have clinical relevance? Retrospective analysis of 1043 embryos - Yung-Liang Liu; Tzu-Ning Yu; Peng-Hui Wang; Chii-Ruey Tzeng; Ching-Hui Chen; Chi-Huang Chen (Elsevier, 2020)
Objective: To determine whether preimplantation genetic testing for aneuploidy (PGT-A) could pick up true abnormalities that have clinical relevance. Materials and methods: This was a retrospective cohort study of patients who underwent in vitro fertilization with PGT-A from 2015 to 2017. We evaluated the associations of aneuploidy and mosaicism with maternal age, the chromosome abnormalities present in individual chromosomes, and the effect of embryo sex on the proportion of each type of error in the four chromosomes most frequently affected. Result(s): A total of 1043 embryos from 255 patients (mean maternal age = 39 ± 4 years) were included in the initial analysis. Of these, 36% (377/1043) were euploid, 47% (487/1043) were aneuploid, 13% (140/1043) contained mosaicism, and 4% (39/1043) gave no result. We excluded the 39 embryos with no result; thus, 1004 embryos were included in the analysis. Increased aneuploidy was associated with increased maternal age, but the rate of embryo mosaicism was not. A combined analysis of aneuploidy with noncomplex abnormalities and mosaicism showed that chromosomes 22, 21, 16, and 15 were the most frequently involved. Chromosome 22 showed the highest proportion of mosaicism and chromosome 15 showed the highest proportion of aneuploidy. When we included embryo sex in the analysis, embryo sex was associated with these chromosome errors in the most susceptible chromosome, 22. Conclusion(s): PGT-A showed that chromosomes 22, 21, 16, and 15 were the most frequently involved among common chromosome abnormalities, comparable with those of published data analyzed from spontaneous abortion. This result suggested that PGT-A could pick up abnormalities that have clinical relevance to spontaneous abortion. Moreover, we identified a role of embryo sex in these chromosomal errors on chromosome 22.